2004
DOI: 10.1007/s00213-003-1766-6
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine reduces nocturnal urinary cortisol excretion in healthy subjects

Abstract: The significant reduction of nocturnal cortisol excretion following quetiapine reflects a decreased activity of the HPA-axis in healthy subjects. This finding may be an important aspect in quetiapine's mode of action in different patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 63 publications
(75 reference statements)
4
17
0
4
Order By: Relevance
“…These results are comparable with the effects of the atypical antipsychotic quetiapine studied under similar conditions [18], but are in contrast with the finding of unchanged cortisol secretion seen after acute administration of amisulpride in healthy subjects [19].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These results are comparable with the effects of the atypical antipsychotic quetiapine studied under similar conditions [18], but are in contrast with the finding of unchanged cortisol secretion seen after acute administration of amisulpride in healthy subjects [19].…”
Section: Discussionsupporting
confidence: 83%
“…In this context, we also found that quetiapine, an atypical antipsychotic with predominant 5-HT2A antagonism relative to its low affinity for the 5-HT2C receptor, also decreases cortisol excretion [18]. Furthermore, the lack of influence on cortisol concentrations observed after the administration of amisulpride [19] is compatible with this mechanism of action of ziprasidone since amisulpride is a selective dopamine D2/D3 receptor blocker without significant activity at 5-HT2 receptors.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Because hypercortisolemia (Cushing's syndrome) leads to insulin resistance, glucose intolerance, high blood pressure, and triglyceridemia, the authors suggested that hypercortisolemia could be the primary defect that leads to the development of the insulin resistance in antipsychotic-naive patients with schizophrenia (27). However, in studies examining the effects of antipsychotic medication on patients with schizophrenia, changes in total plasma cortisol levels have generally not been measured or have been an inconsistent finding (27,28).…”
Section: Discussionmentioning
confidence: 99%